Bacterial contamination of the small intestine is an important cause of occult malabsorption in the elderly. Issue 6395 (17th September 1983) - McEvoy, A; Dutton, J; James, O F
Abstract : A study was conducted to examine the contribution that occult malabsorption makes to malnutrition among elderly patients admitted to an acute geriatric ward. Malnutrition was defined by anthropometric, haematological, and biochemical measurements. Out of 490 patients, 55–many of whom had presented with non-gastrointestinal symptoms–were found to be malnourished. In 31 poor diet alone was probably the cause, but in the remaining 24 patients previously unrecognised malabsorption was detected. Of these patients, 17 were found to have bacterial contamination of the small bowel (nine with duodenojejunal diverticula, four after gastric surgery, and four diagnosed as contamination with "no sump"). In 10 patients contamination was confirmed by culture of intestinal juice: Escherichia coli was predominant in nine cases, and anaerobic organisms in one. Small bowel bacterial overgrowth without a "blind loop" or obvious underlying cause has not previously been fully proved in the elderly. Coeliac disease was detected in two patients, and chronic pancreatitis in two. Occult malabsorption is an important cause of malnutrition in the elderly. Such malnutrition not infrequently occurs in geriatric patients presenting to hospital with non-specific symptoms of physical deterioration.